Reporting model for decision support based on the SAF-T standard - Vicente, L. B.; O'Neill, H.; Pinho, V. (17.ª Conferência da Associação Portuguesa de Sistemas de Informação (CAPSI’2017), 2017)
The purpose of this paper is to summarize the results and conclusions obtained during an investigation aiming to reveal the usefulness and added value of the SAF-T when used to support decision making and the internal management of organizations. The research addresses the SAF-T standard as a source of knowledge for decision support and intelligent auditing. The research contextualizes the contribution of the SAF-T based model as a scalable way to make intelligent audits, implement new business processes and manage electronic control. The information quality of this report and digital model is also stressed. Upon automatic reporting based on SAF-T data one can draw financial conclusions and decide changes on a firm´s commercial scope. This article also highlights the advantages of decision making based on the proposed model and report. A set of hints and suggestions for further research work on this topic is also provided.